Relationship Between Organisational Culture and Customer Focus on Operational Performance: An Agile Manufacturing Approach - Sutrisno; Yudha, Afiff; Narto (Journal Knowledge Industrial Engineering (JKIE), 2026)
This paper aims to empirically test the relationships between organizational culture and customer focus, and their impact on operational performance in shipbuilding companies in the context of agile manufacturing. This research used a quantitative PLS-SEM method, with 155 respondents from 27 shipbuilding companies in Indonesia, collected via an online survey using random sampling. The results showed that organizational culture does not directly influence operational performance. Meanwhile, customer focus significantly affects operational performance, and it also mediates the relationship between organizational culture and operational performance. This study fills a gap in manufacturing strategy by adopting an agile manufacturing approach to improve the operational performance of shipbuilding companies, which is measured by indicators of construction time, quality, construction cost, and sales revenue. Besides, this study contributes empirical evidence on the relationship between organizational culture and customer focus, and their impact on operational performance in shipbuilding companies.